Drop dead - Chu, Lily (Sourcebooks Casablanca, 2025)
"Obituary writer Nadine Barbault doesn't mind being called "Lady Death." It suits the ice queen persona she's cultivated to survive the fast-paced Toronto Herald. So when Nadine learns that famous (and reclusive) author Dot Voline has died, she doesn't hesitate to run the obituary...only to discover that Dot is very much alive. Nadine's screw-up has brought Wesley Chen of the rival Spear no end of joy-she's been a thorn in his extremely ambitious side for years. But the renewed interest in Dot also surfaced chatter about a mysterious past scandal. Intrigued, Wes goes to the source to learn more-only to discover Nadine had the exact same idea...and the infuriating woman isn't willing to respect dibs. Typical. At first, Dot refuses to speak to either of the squabbling pair, but then they receive an unusual request-work together, and Dot will share everything. The offer seems too good to be true...and of course, it is: in a bitter twist of irony, Dot dies for real before she can finish recounting her story. Not all is lost, however. The estate's executor allows Wes and Nadine access to Dot's sprawling wonderland of a mansion for three weeks to find their answer."--